Medical education in sub-Saharan Africa: a literature review - Sewankambo, Nelson (Willey, 2011)
Objectives This review synthesises research published in the traditional and ‘grey’ literature to promote a broader understanding of the history and current status of medical education in sub-Saharan Africa (SSA). Methods We performed an extensive review and analysis of existing literature on medical education in SSA. Relevant literature was identified through searches of five traditional medical databases and three non-traditional or grey literature databases featuring many African journals not indexed by the traditional databases. We focused our inquiry upon three themes of importance to educators and policymakers: innovation; capacity building, and workforce retention. Results Despite the tremendous heterogeneity of languages and institutions in the region, the available literature is published predominantly in English in journals based in South Africa, the UK and the USA. In addition, first authors usually come from those countries. Several topics are thoroughly described in this literature: (i) human resources planning priorities; (ii) curricular innovations such as problem-based and community-based learning, and (iii) the ‘brain drain’ and internal drain. Other important topics are largely neglected, including: (i) solution implementation; (ii) programme outcomes, and (iii) the development of medical education as a specialised field of inquiry. Conclusions Medical education in SSA has undergone dramatic changes over the last 50 years, which are recorded within both the traditionally indexed literature and the non-traditional, grey literature. Greater diversity in perspectives and experiences in medical education, as well as focused inquiry into neglected topics, is needed to advance medical education in the region. Lessons learned from this review may be relevant to other regions afflicted by doctor shortages and inequities in health care resulting from inadequate capacity in medical education; the findings from this study might be used to inform specific efforts to address these issues.
Keywords: Medical education; Africa; Sub-Saharan